2018
DOI: 10.2147/dhps.s133286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cardiac risk: exposure response analysis in early clinical drug development

Abstract: The assessment of a drug’s cardiac liability has undergone considerable metamorphosis by regulators since International Council for Harmonization of Technical Requirement for Pharmaceuticals for Human Use E14 guideline was introduced in 2005. Drug developers now have a choice in how proarrhythmia risk can be evaluated; the options include a dedicated thorough QT (TQT) study or exposure response (ER) modeling of intensive electrocardiogram (ECG) captured in early clinical development. The alternative approach o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…However, CRA is now being used and increasingly accepted as an alternative to the IUT to evaluate the presence of a QTc safety signal and can be part of the body of evidence regarding arrhythmia risk prediction and decision-making. This enhanced role has been profiled in reviews by Grenier et al 11 and Garnett and colleagues. 9 When CRA is used to estimate a drug's risk, the upper bound of the 2-sided 90% confidence interval around the estimated maximal effect on QTc should be less than 10 milliseconds at the highest clinically relevant exposure to conclude that the investigative product is low risk and expanded ECG collection in later-phase studies is not essential.…”
Section: Historical Background: the Qt And Herg-centric Modelsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, CRA is now being used and increasingly accepted as an alternative to the IUT to evaluate the presence of a QTc safety signal and can be part of the body of evidence regarding arrhythmia risk prediction and decision-making. This enhanced role has been profiled in reviews by Grenier et al 11 and Garnett and colleagues. 9 When CRA is used to estimate a drug's risk, the upper bound of the 2-sided 90% confidence interval around the estimated maximal effect on QTc should be less than 10 milliseconds at the highest clinically relevant exposure to conclude that the investigative product is low risk and expanded ECG collection in later-phase studies is not essential.…”
Section: Historical Background: the Qt And Herg-centric Modelsmentioning
confidence: 79%
“…However, CRA is now being used and increasingly accepted as an alternative to the IUT to evaluate the presence of a QTc safety signal and can be part of the body of evidence regarding arrhythmia risk prediction and decision‐making. This enhanced role has been profiled in reviews by Grenier et al 11 and Garnett and colleagues. 9 …”
Section: Updated Responses To Questions Regarding Study Designs Of New Pharmaceuticals Based On the Original 2015 Qanda (R3) Draft Documementioning
confidence: 79%
“…The second major development in QT liability assessment involves the use of exposure response analysis (ER) or concentration QT modelling (cQT) [86,87]. This type of analysis was under investigation in 2003 and became an integral part of TQT trials in 2006 albeit as a secondary analysis tool relative to the primary central tendency by time point approach known as the Intersection Union Test (IUT) as detailed in ICH E14.…”
Section: Current Fda Guidance For Assessing Qt Liabilitymentioning
confidence: 99%
“…This model easily accounts for time dependent effects, covariates such as age, gender, ethnicity and hence is flexible. 16 ER analysis is useful in scenarios such as when there is QTc prolongation when drug is used at lower dose than in a TQT study, QTc prolongation in an underpowered study and during evaluation of the assay sensitivity of a positive control. 16 To demonstrate the advantage of ER modelling, let us take the example of the analysis of TQT studies done on a drug -losmapimod (product of GlaxoSmithKline), the drug was shown to cause a larger QT prolongation than the supratherapeutic dose, besides not showing any efficacy.…”
Section: Exposure-response (Er) Modelling Of Ecgsmentioning
confidence: 99%
“…16 ER analysis is useful in scenarios such as when there is QTc prolongation when drug is used at lower dose than in a TQT study, QTc prolongation in an underpowered study and during evaluation of the assay sensitivity of a positive control. 16 To demonstrate the advantage of ER modelling, let us take the example of the analysis of TQT studies done on a drug -losmapimod (product of GlaxoSmithKline), the drug was shown to cause a larger QT prolongation than the supratherapeutic dose, besides not showing any efficacy. When ER analysis was done using concentration of the drug and QTc, it showed that the false positive results was due to multiple dosing of the drug which had resulted in shift of the baseline.…”
Section: Exposure-response (Er) Modelling Of Ecgsmentioning
confidence: 99%